Efficacy and safety of oral anticoagulation in elderly patients with atrial fibrillation - Cavallari, Ilaria (Anatol J Cardiol, 2018)
Elderly patients with atrial fibrillation are at a higher risk of both ischemic and bleeding events compared with younger patients; therefore, balancing risks and benefits of antithrombotic strategies in this population is crucial. Recent studies have shown that because the risk of stroke increases with age more than the risk of bleeding, the absolute benefit of oral anticoagulation is the highest in elderly patients in whom it outweighs the risk of bleeding. Direct oral anticoagulants (DOACs) have been developed as a treatment for the prevention of cardioembolic stroke to overcome some limitations of warfarin, such as the need for frequent monitoring, labile INR values requiring frequent dose adjustment, dietary and drugs interactions, and increased risk of intracranial bleeding. Despite the better safety profiles of DOACs compared with warfarin, elderly patients often remain undertreated because of the fear of bleeding complications. This review summarizes current evidence regarding the risks of thromboembolisms and bleeding in different antithrombotic strategies in elderly patients (aged ≥75 years) with atrial fibrillation, including data from the warfarin-controlled phase 3 DOACs trials.